Removal of COD Using Delonix Regia Pods Activated Carbon Adsorbent for Natural Rubber Wastewater Treatment - Daud, Zawawi; Ahmad, Baharin; Awang, Halizah; Abubakar, Mahmoud Hijab; Ridzuan, Mohd Baharudin; Tajarudin, Husnul Azan (International Journal of Integrated Engineering, 2019)
Plant waste such as Delonix Regia Pods have the potential to be used as absorbents. A study of activated carbon derived from delonix regia pods was carried out for the removal COD in natural rubber wastewater. Sample wastewater was obtained from the rubber processing industry and characterized to determine the level of pollutant content. Results of the analysis of wastewater characterization shows that the COD value was 5196 mg/L which is above discharge standards. Laboratory experiments was conducted to determine the optimum dosage, pH, shaking speed and contact time using response surface methodology. The results showed that the optimal dosage, pH, shaking speed and contact time were 4 g, pH 8, 150 rpm and 100 minutes with COD removal value of 70.65 %. The model F-value obtained for COD was 68.27 with the Prob. > F value of < 0.0001 indicating the significance of the model. The predicted versus the empirical data were relatively close to each other, therefore the developed models sufficiently described the response and variables interaction in the adsorption process. The results also indicate the suitability of the adsorbent for application in a sustainable wastewater treatment. It is recommended that further study be carried out to assess its application for other pollutants derived from non-rubber industries.